(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
A major problem in the use of renewable energy sources is to increase the energy efficiency of their operation. Automation and selection of the optimal process flow diagram allow increasing this energy efficiency. The article examines the features of automation of a solar collector with forced circulation of the coolant and various types of wind turbines along the channel for converting wind energy into electricity. It is concluded that in the event of an increase in the production of electrical energy due to distributed generation (wind energy, solar energy) in the power system, it is necessary to provide for appropriate measures to compensate for the randomly generated electrical power that changes.